Integrating human factors training into safety management and risk management: A case study from aviation maintenance. (June 2015) - Cromie, Samuel; Ross, Derek; Corrigan, Siobhan; Liston, Paul; Lynch, Darragh; Demosthenous, Evangelos
Aviation is facing the challenge of integrating new regulatory requirements on safety management systems with a range of existing processes addressing human factors in line with regulations. This article presents an approach to using mandated human factors continuation training as a tool for risk management within the safety management system. A three-phase blended learning programme was designed to address identified human and organisational hazards within the operation, to enhance knowledge and application of risk management strategies, and to build a stronger safety culture within the operation. The article outlines how the programme is designed to address regulatory, organisational and pedagogical requirements. The 'Wobbly Steps' concept, which is elaborated in this article, is used as a central metaphor for conveying the link between organisational resources and individual risky behaviours or unsafe acts. The training programme is embedded in an evaluation process designed to guide the effective design, development and delivery of the programme as well as assessing the impact of the training on the safety culture and performance of the operation.